Modern functioning aspects of the Society for Worldwide Interbank Financial Telecommunications - O. B. Anikin; D. D. Mishchenko (Вестник университета, 2023)
The modern SWIFT system is the most popular method of transnational transactions, which confirms the relevance of the chosen topic. The purpose of this article is to consider modern aspects of the SWIFT system functioning as a tool for carrying out bank transfers and economic pressure. The study subject is the SWIFT. The article uses such theoretical research methods as analysis and synthesis. The article contains an analysis of technological innovations in 2017–2022 and of SWIFT’s structure, the method of its operation, as well as an analysis of the role of the system in economic pressure on the example of Iran and Russia. The article can be applied when studying the principle of operation and the role of SWIFT in international transactions. The SWIFT regularly improves the standards and methods of its work, introduces innovations, so it is possible to talk about its long-term global prospects. The study resulted the identification of such innovations as SWIFT gpi, SWIFT Go, gpi Tracker and others, which indicates the constant updating, development of the system, that adapts to the changing consumer demand. The findings highlight the global role of the SWIFT system in transnational payments and economic impact.